Changes in weekend and weekday care quality of emergency medical admissions to 20 hospitals in England during implementation of the 7-day services national health policy. Issue 7 (28th October 2020) - Bion, Julian; Aldridge, Cassie; Girling, Alan J; Rudge, Gavin; Sun, Jianxia; Tarrant, Carolyn; Sutton, Elizabeth; Willars, Janet; Beet, Chris; Boyal, Amunpreet; Rees, Peter; Roseveare, Chris; et al.
Abstract : Background: In 2013, the English National Health Service launched the policy of 7-day services to improve care quality and outcomes for weekend emergency admissions. Aims: To determine whether the quality of care of emergency medical admissions is worse at weekends, and whether this has changed during implementation of 7-day services. Methods: Using data from 20 acute hospital Trusts in England, we performed randomly selected structured case record reviews of patients admitted to hospital as emergencies at weekends and on weekdays between financial years 2012–2013 and 2016–2017. Senior doctor ('specialist') involvement was determined from annual point prevalence surveys. The primary outcome was the rate of clinical errors. Secondary outcomes included error-related adverse event rates, global quality of care and four indicators of good practice. Results: Seventy-nine clinical reviewers reviewed 4000 admissions, 800 in duplicate. Errors, adverse events and care quality were not significantly different between weekend and weekday admissions, but all improved significantly between epochs, particularly errors most likely influenced by doctors (clinical assessment, diagnosis, treatment, prescribing and communication): error rate OR 0.78; 95% CI 0.70 to 0.87; adverse event OR 0.48, 95% CI 0.33 to 0.69; care quality OR 0.78, 95% CI 0.70 to 0.87; all adjusted for age, sex and ethnicity. Postadmission in-hospital care processes improved between epochs and were better for weekend admissions (vital signs with National Early Warning Score and timely specialist review). Preadmission processes in the community were suboptimal at weekends and deteriorated between epochs (fewer family doctor referrals, more patients with chronic disease or palliative care designation). Conclusions and implications: Hospital care quality of emergency medical admissions is not worse at weekends and has improved during implementation of the 7-day services policy. Causal pathways for the weekend effect may extend into the prehospital setting.